Effects of weighted rope jump training on anaerobic power, speed, flexibility and agility in adolescent volleyball players - Colakoglu, F. F.; Atalay Guzel, N.; Karacan, S.; Baltaci, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The aim of this study was to investigate the effect of a 12-week rope jumping and weighted rope jumping exercise programme on anaerobic power, speed, flexibility and agility performance of female adolescent volleyball players. Methods Twenty-five female volleyball players (mean age: 14,66±1,16yrs) who had at least 2 years volleyball experience participated in this study and were divided into there groups. Group 1 took on the weighted rope jumping (WRJ; (n=8)) programme as well as volleyball training, Group 2 on rope jumping (RJ; (n=9)) programme as well as volleyball training and Group 3, the control (C; (n=8)) participated only volleyball training. The exercise sessions were carried out 3 times each week for 12 weeks. The anaerobic power of the subjects was measured by using vertical jump test. 30 m. sprint test, seat and reach test, hexagonal obstacle and zigzag tests were applied to the subjects as described in the literature. Data indicating the effects of these exercise programs on the performance parameters and somatotype was statistically analyzed by ANOVA and Kruskal-Wallis test. Results: There was a significant difference a considerable increase in the values of flexibility and anaerobic power at the end of training of the two groups (p<0,01). Also speed and agility performance of two groups were significantly different at the end of training (p<0,01). Compared to control and training groups, the values of WRJ group were highly increased for the mean of anaerobic power and zig-zag test (p<0,01). Discussion: As a result; we showed that performance parameters of the groups taking 12-week weighted rope jump exercise programme would be considerable improved. Therefore, the results of this study indicate that a weighted rope jumping exercise programme has a potential improvement anaerobic power and agility of volleyball players.